Foreign experience of small and medium-sized enterprises in managing innovation activities - Aibossynova, D. (Journal of Economic Research & Business Administration, 2021)
The article considers the international experience of managing the innovation activities to small and medium-sized enterprises (later - SMEs). The analysis shows that despite the presence of certain disadvantages, in foreign practice the SMEs are considered as the main source of innovative development of the economy, due to the preponderance of the advantages of these businesses. Studying the experience of innovation activities of countries involves identifying the main processes of updating the economy of Kazakhstan and guaranteeing its confident entry into the world community. The state level is a national innovation management system, consisting of many elements, such as: regulatory, financial, economic, organizational, social, etc. The task of the state in implementing the management of innovative activity of SMEs is to maintain a flexible balance between state regulation and free enterprise initiative. In other words, in providing effective, market and competitive conditions for the development of the innovation market, while carrying out the necessary functions of state regulation. It must be a dynamic process that is responsive to market changes. This is manifested in budget, grant, project, program and targeted financing, state stimulation of innovative technologies within the framework of the state order for innovative products and the provision of tax benefits for SMEs whose activities are aimed at research and development (R&D) and innovation. At the entrepreneurial level, the existing traditional administrative methods for managing the activities of SMEs will not be sufficient, since intellectual and knowledge will be the determining resources here. The use of human intellectual abilities in the creation of innovations in order to enhance the competitiveness of SMEs is the main function of innovation. To manage such a resource, it is necessary, first of all, to create an innovative environment for it in which subjects of innovative small and medium-sized businesses operate. Key words: international experience, innovation activities management, small and medium-sized enterprises, governmental support, innovative enterprises.